2016
DOI: 10.4103/0019-5049.195487
|View full text |Cite
|
Sign up to set email alerts
|

Comparative randomised study of GlideScope® video laryngoscope versus flexible fibre-optic bronchoscope for awake nasal intubation of oropharyngeal cancer patients with anticipated difficult intubation

Abstract: Background and Aims:Awake flexible fibre-optic bronchoscope (FFS) is the standard method of intubation in difficult airway in oral cancer patients. We decided to evaluate GlideScope® video laryngoscope (GL) for intubation as compared to the standard FFS for nasal intubation in such patients.Methods:After the ethical committee approval, we included 54 oropharyngeal cancer patients divided randomly into two equal groups: Group G and Group F. After pre-medication and pre-oxygenation, awake nasal intubation was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 9 publications
(11 reference statements)
2
26
0
Order By: Relevance
“…) demonstrated no significant difference in the number of failed intubations between the groups. Similarly, analysis of the six studies (391 participants) that reported on the number of successful intubations on the first attempt showed no difference between the groups (Fig. ).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…) demonstrated no significant difference in the number of failed intubations between the groups. Similarly, analysis of the six studies (391 participants) that reported on the number of successful intubations on the first attempt showed no difference between the groups (Fig. ).…”
Section: Resultsmentioning
confidence: 82%
“…Eight studies were eventually included in our review . We excluded one study from the meta‐analysis due to incomplete data reporting .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these studies showed that as with awake fiberoptic intubation, awake VL-assisted intubation achieved a high success rate, satisfactory intubation times, and a high acceptance of patients and anesthesiologists. Thus, it is concluded that in patients with predicted and known difficult intubations, awake VL-assisted intubation represents an acceptable alternative to awake fibreoptic intubation (36)(37)(38)(39)(40).…”
mentioning
confidence: 99%